SOME ISSUES OF IMPROVING THE PROCEDURE FOR ORGANIZING THE ACTIVITY OF A TRAINEE ADVOCATE - Matmurotov Alibek Ravilovich (Scholar Express Journals, 2024)
In this article, the requirements for becoming an advocate trainee, the possibilities of introducing a register of advocate trainees, and the requirements for the trainee manager are studied and analyzed based on the positive experience of foreign countries. In addition, the author analyzed the issues of introducing the register of internship managers and expanding the rights and obligations of internship managers in order to find highly qualified internship supervisors for persons applying for the status of attorney to become qualified attorneys and create an opportunity for internship under their leadership.
Keywords: Advocate trainee; trainee supervisor; requirements for trainee advocate